FAKTOR-FAKTOR YANG MEMPENGARUHI FERTILITAS PADA PASANGAN YANG MENIKAH DIUSIA DINI DI KABUPATEN SIJUNJUNG - Refrihardi Refrihardi; Dewi Zaini Putri (Universitas Negeri Padang, 2019)
This study aims to analyze the impact of (1) wife's education (2) family planning (3) wife's age (4) husband's work status (5) wife's work status (6) household income (7) mortality (8) residence to fertility early age couples in Sijunjung Regency. The data analysis tool used is logistic regression using 2017 Susenas data from the Central Statistics Agency (BPS). The study population was households that married at an early age and had children. The sample used was 226households categorized as having more than 2 children and small children with 2 children. The hypothesis test used is the G test and the Wald test with a real level of 10%. The results of the Logistic Regression found that family planning, type of wife's age, household income, and mortality had an influence on the fertility of early age couples in Sijunjung District. Therefore, the community is expected to conduct a marriage at a mature and productive age so that there are no future problems that result in high fertility. Because when households have more than 2 children there are economic problems that affect poverty and population density in Sijunjung District.